Bioanthropological and Biomechanical Perspectives on Skeletal Senescence Variation - Alaydrus, Sayf Muhammad; Jauhari, Muhamad Andri (Universitas Airlangga, 2024)
Background: Senescence is the deterioration of the body's biological and physiological function throughout later life. Senescent populations are more prone to diseases. However, aside from osteoporosis, skeletal senescence is a less discussed topic in Indonesia. A global and national increase in the aging population indicates they will be a major group in society, raising the urgency of reviewing this matter. This study aims to comprehend the physiological and biomechanical mechanisms of skeletal senescence, as well as senescent variations in certain sex and population affinities. Literature Review: Age-related skeletal cellular death and imbalance contributes to bone damage in elders. Senescence also affects skeletal biomechanics, expressed in increased bone porosity and brittleness. Stresses in aged bone risks straining above its elastic limit and causing fractures due to its inability to tolerate such stresses. The loss of sex hormones is related to skeletal senescence, especially in females, while the effects of testosterone on skeletal senescence are under-researched. Dietary change, estrogen replacement therapy, and calcitonin consumption are effective measures in reducing the effects of osteoporosis. Variations were found in the bone aging process in different populations, especially regarding bone mineral density loss in white, African-American, Asian, and Hispanic populations. Conclusion: Specific population-based healthcare services in geriatrics and gerontology are highly suggested to ensure inclusive healthcare for every aged individual. Due to the minimal data about bone aging in Indonesia (other than osteoporosis), the authors encourage data procurement from the local populations to create more suitable medical guidelines for elders in Indonesia.